The effect and mechanism of millepachine-disrupted spindle assembly in tumor cells. Issue 5 (June 2018) - Wu, Wenshuang; Liu, Feng; Su, Anping; Gong, Yanping; Zhao, Wanjun; Liu, Yang; Ye, Haoyu; Zhu, Jingqiang
Abstract : Millepachine (MIL) is a bioactive natural product that shows great potential for cancer treatment. Previous studies showed that MIL was a novel cancer drug candidate with a special structure. To provide reference for the research and development of MIL, we further investigated the mechanism of MIL inducing G2/M arrest and found MIL disrupted spindle assembly in tumor cells. In this study, we investigated the disrupting spindle assembly effects of MIL with a focus on its potential mechanism of action. First, we indicated that MIL did not inhibit microtubule polymerization from the results of in-vivo microtubule nucleation assay and microtubule polymerization in-vitro assay but delayed this process by inhibiting the production of ATP in tumor cells. Thereafter, we investigated the effect of MIL on the mitotic spindle. We found that MIL induced multipolar spindles by inhibiting the activity of Eg5 and inhibited mitotic spindle formation and chromatin condensation by the activation of the spindle assembly checkpoint (SAC) in tumor cells. These results established a novel function of MIL in regulating the assembly of mitotic spindle. As Eg5 and SAC are antitumor targets, effect of MIL on the Eg5 protein and SAC activation hinted that MIL has novel application in the development of antitumor drugs.